2017
DOI: 10.1111/eea.12531
|View full text |Cite
|
Sign up to set email alerts
|

Longevity and fecundity of the egg parasitoid Telenomus podisi provided with different carbohydrate diets

Abstract: In order for successful biological pest control using parasitoids, the most suitable naturally available food resources, as well as the fitness of parasitoids feeding on these resources, need to be ascertained. The goal of this study was to improve the understanding of the ecological requirements and consequent fitness of one such parasitoid, Telenomus podisi Ashmead (Hymenoptera: Platygastridae), a predominant stink bug (Heteroptera: Pentatomidae) egg parasitoid native to southeastern USA. We assessed the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
(68 reference statements)
0
10
0
2
Order By: Relevance
“…In addition, sugar supplementation has repeatedly been shown to enhance parasitoid lifespan ( e.g. Lee, Heimpel, & Leibee, 2004; Chen & Fadamiro, 2006; Zhu et al, 2013; Wang et al, 2014; Lahiri, Orr, Cardoza, & Sorenson, 2017), whereas it is generally assumed not to contribute significantly to egg production (Jervis, Ellers, & Harvey, 2008; Rivero & Casas, 1999; Visser & Ellers, 2008). This is especially true in pro‐ovigenic parasitoids in which females emerge with their full egg supply and do not produce additional eggs during their lifetime (Jervis, Heimpel, Ferns, Harvey, & Kidd, 2001; Rivero & Casas, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sugar supplementation has repeatedly been shown to enhance parasitoid lifespan ( e.g. Lee, Heimpel, & Leibee, 2004; Chen & Fadamiro, 2006; Zhu et al, 2013; Wang et al, 2014; Lahiri, Orr, Cardoza, & Sorenson, 2017), whereas it is generally assumed not to contribute significantly to egg production (Jervis, Ellers, & Harvey, 2008; Rivero & Casas, 1999; Visser & Ellers, 2008). This is especially true in pro‐ovigenic parasitoids in which females emerge with their full egg supply and do not produce additional eggs during their lifetime (Jervis, Heimpel, Ferns, Harvey, & Kidd, 2001; Rivero & Casas, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Irvin & Hoddle (2015) melaporkan progeni parasitoid Anagyrus pseudococci (Girault) meningkat berturut-turut 132% dan 152% jika induk betina parasitoid disediakan nektar dari bunga soba (Fagopyrum esculentum Moench) dan ekstraflora dari tanaman Vicia sativa L. dibandingkan dengan yang hanya diberi air. Parasitoid Telenomus podisi Ashmead (Hymenoptera: Platygastridae) yang diberi embun madu dari kutu daun Aphis craccivora Koch (Hemiptera: Aphididae) memiliki masa hidup dan keperidian yang sama dengan yang diberi nektar bunga soba dan madu (Lahiri et al 2017). Dengan demikian, pemahaman tentang kebutuhan nutrisi parasitoid merupakan hal penting dalam upaya penataan lanskap pertanian yang menunjang kehidupan parasitoid.…”
Section: Pembahasanunclassified
“…In addition to feeding on host hemolymph, parasitoid females require sugar food sources such as floral nectar and/or honeydew in order to sustain biological traits linked to actual parasitoid fitness (Jervis et al 2001;Wäckers et al 2008;Benelli et al 2017). Honeydew consumption has been shown to increase parasitoid longevity (Hogervorst et al 2007;Hagenbucher et al 2014;Tena et al 2018) and may be involved in parasitoid performance, e.g., by increasing offspring production (Lahiri et al 2017;Dong et al 2018;Picciau et al 2019); this has notably been reported for N. artynes feeding on floral nectar (Balzan and Wäckers 2013) as well as for N. tutae feeding on whitefly honeydew (Dong et al 2018). We demonstrate further that tomato aphid honeydew enhances N. tutae adult longevity under laboratory conditions (Fig.…”
Section: Impact Of Honeydewmentioning
confidence: 99%